THE ENLIGHTENMENT JADID MOVEMENT IN CENTRAL ASIA AT THE BEGINNING OF THE 20TH CENTURY (The Journal of Interdisciplinary Human Studies, 2026)
This article is devoted to the jadid movement went through hard timesin a historical multi-faceted way. Jadidism became the arena of struggle of variousphilosophies and worldly methods of approach to perspectives of social development. Itfocused on key questions about social development: the conceptual sense of the ideologyof breaking the basic foundations of feudalism and colonialism.
Keywords: Education, jadidism, historical, Turkestan, reforming movement, parliamentarism.